The role of customs policy in maximizing the benefits of economic blocs: The case of Egypt - Mahmoud Magdy Barbary; Abdalla Ramadan Tawfiq (Economies, 2024)
This study aims to examine the relationship between customs policy and the economic blocs of which Egypt is a member, with a focus on the theory of New Regionalism and modern trends in customs policies. Egypt joined numerous economic blocs following its accession to the world trade organization (WTO) in 1995, yet this membership has not yielded significant positive impacts on the performance of Egyptian exports or the trade balance. The study utilized panel data analysis of Egypt's international trade from 2001 to 2023. The results indicate that, despite Egypt's limited success in reaping the benefits of most economic blocs, largely due to the concentration of Egyptian exports in primary and agricultural products and the low tariff rates, factors such as customs clearance processes, tariff barriers, non-tariff barriers, regional trade agreements, and technology adoption still play a crucial role in influencing trade volume among member countries. The findings highlight the significance of effective customs procedures and the reduction of trade barriers in boosting trade volumes within regional trade agreements. The study proposes a strategy for Egypt's customs policy to maximize benefits from economic blocs, focusing on four key areas: aligning customs policy planning with targeted export sectors to realize trade creation and trade diversion effects; fully implementing trade facilitation programs and liberalizing customs policy procedures; adopting a national strategy to stimulate high value-added export industries as a long-term solution; and adopting regional trade agreements that support cumulative origin as a short-term solution.
Keywords: F2; F13; F15; 330; balance of payments; customs policy; economic blocs; tariffs